Effects of Temperature on the Leaching Behavior of Pb from Cement Stabilization/Solidification-Treated Contaminated Soil - Wang, Ping; Liu, Xialin; Zeng, Gang; Ma, Jiangfeng; Xia, Feng (Separations, 2022)
Solidification/stabilization (S/S) is one of the most widely used techniques in the disposal of heavy-metal-contaminated soil, though the long-term effectiveness of S/S technology remains implicit. Temperature is an important factor affecting the leaching behavior of heavy metals and the long-term effectiveness of S/S treatment. This study systematically explored the influence of temperature on the leaching behavior of lead in an S/S monolith through semi-dynamic leaching test at different temperatures. The results showed that an increase in temperature could accelerate the leaching concentration and cumulative leaching amount of lead ions in the S/S monolith. The cumulative leaching amount of lead ions in the S/S monolith after 11 days at 55 °C was about 5.8 times that at 25 °C. The leaching rate of lead ions in the S/S monolith increased with the increase in temperature. The leaching index of lead ions was larger than 9, which met the requirements for “controlled utilization” in the environment. The leaching mechanism of lead ions was diffusion control and did not change in the temperature range of 25–55 °C. These findings indicate that temperature affects the leaching behavior and the long-term effectiveness of S/S treatment, and temperature variation should be considered in the effectiveness evaluation of S/S treatment.